2021
DOI: 10.1016/j.psep.2021.07.012
|View full text |Cite
|
Sign up to set email alerts
|

2-D modeling to understand the design configuration and flow dynamics of Pond-In-Pond (PIP) wastewater treatment system for reuse

Abstract: Water reuse for irrigation is increasingly recognized as an essential and economical strategy in areas with water scarcity. A simple, low cost, low-maintenance, and highly efficient Pond-In-Pond (PIP) treatment system can be used for wastewater reuse. PIP is a treatment technology in which two types of ponds --anaerobic and aerobic --are combined into a single pond and consists of a deeper inner section entirely submerged within the outer pond. Previous studies on PIPs and PIP-like systems have reinforced the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The pond-in-pond wastewater treatment system, in which anaerobic and aerobic ponds are combined into a single pond, was also proposed for water reuse. This system is considered highly efficient, with low costs and low maintenance [47]. Xing et al (2021) revealed that the integrated chlor(am)ine-UV oxidation and UF may be considered a promising alternative for efficient wastewater recycle and reuse [48].…”
Section: Tertiary Treatment (Tt)mentioning
confidence: 99%
“…The pond-in-pond wastewater treatment system, in which anaerobic and aerobic ponds are combined into a single pond, was also proposed for water reuse. This system is considered highly efficient, with low costs and low maintenance [47]. Xing et al (2021) revealed that the integrated chlor(am)ine-UV oxidation and UF may be considered a promising alternative for efficient wastewater recycle and reuse [48].…”
Section: Tertiary Treatment (Tt)mentioning
confidence: 99%
“…Dynamic simulation of biochemical wastewater treatment allows for a thorough understanding of treatment processes through mathematical modelling (Al‐Wardy, Alquzweenib, & Al‐Saadi, 2021; Faris et al, 2022; Henze et al, 2000; Mu'azu, Alagha, & Anil, 2020). To lessen the disparities between modelling the output and real treatment results, activated sludge systems have been designed and optimized and their performance has been assessed using mathematical models (Adhikari, Fedler, & Asadi, 2021; Al‐Wardy, Alquzweenib, & Al‐Saadi, 2021; Faris et al, 2022). Among the several steady‐state and dynamic mathematical models that describe the ASP, the activated sludge model (ASM) is a recognized model in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The model simulation provides a valuable and effective tool to optimize complicated biological treatment processes. It has been recognized as an indispensable tool in redesigning and managing existing wastewater treatment plants 15 . Numerous commercial numerical simulation software (e.g., Simba, TOXCHEM, GPS-X, BioWin, and WEST) have incorporated activated sludge models (e.g., ASM1, ASM2, ASM2d, and ASM3) have been developed for engineering practices 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%